2004
DOI: 10.1128/aem.70.2.1145-1150.2004
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection of Contaminated Water by Using Solar Irradiation

Abstract: Contaminated water causes an estimated 6 to 60 billion cases of gastrointestinal illness annually. The majority of these cases occur in rural areas of developing nations where the water supply remains polluted and adequate sanitation is unavailable. A portable, low-cost, and low-maintenance solar unit to disinfect unpotable water has been designed and tested. The solar disinfection unit was tested with both river water and partially processed water from two wastewater treatment plants. In less than 30 min in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(48 citation statements)
references
References 16 publications
2
45
0
1
Order By: Relevance
“…A nível doméstico a fervura e o uso de compostos de cloro são comumente utilizados para desinfecção. Caslake et al (2004) ressaltam que a falta de recursos e de infraestrutura de distribuição torna a aplicação de métodos como a cloração caseira extremamente limitada nos países em desenvolvimento, em que os casos de doenças de veiculação hídrica são elevados. Quanto à fervura, o gasto energético é muito alto sendo necessário o consumo de 1 kg de madeira para cada litro de água.…”
Section: Introductionunclassified
“…A nível doméstico a fervura e o uso de compostos de cloro são comumente utilizados para desinfecção. Caslake et al (2004) ressaltam que a falta de recursos e de infraestrutura de distribuição torna a aplicação de métodos como a cloração caseira extremamente limitada nos países em desenvolvimento, em que os casos de doenças de veiculação hídrica são elevados. Quanto à fervura, o gasto energético é muito alto sendo necessário o consumo de 1 kg de madeira para cada litro de água.…”
Section: Introductionunclassified
“…The use of sunlight for supplying healthy water is not a new phenomenon. It has been demonstrated that solar disinfection inactivates microorganism by direct exposure is volume independent economic process and avoids production of hazardous by-products of chemically driven technologies [13]. Solar radiation removes a broad range of microorganisms such as viruses, bacteria and protozoa [14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies carried out by Acra et al (1997) proved the bactericidal effect of the solar UV rays in water disinfection. Wegelin et al (1994), Joyce et al (1996), Solarte et al (1997), Saitoh and El-Ghetany (2002), and Caslake et al (2004) evaluated the synergism between UV exposition, water temperature, and turbidity in disinfection of water for human consumption. McGuigan et al (1998) and Oates et al (2003) reported that it is possible to achieve 100% E. coli inactivation in less than 8 h of solar exposition.…”
mentioning
confidence: 99%